Eksplorasi Metakognisi dan Resiliensi Matematis Mahasiswa dalam Menyelesaikan Masalah Program Linier: Confirmatory Factor Analysis (CFA) - Fithria Ulfah; Mega Suliani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2026)
Metacognition and mathematical resilience are two key contributing factors in enhancing students’ ability to solve problems. However, limited research has explored how these two factors interact and influence one another. This study aims to investigate the relationship between students’ mathematical resilience and metacognition in solving linear programming problems. The research employs a mixed-method approach with an explanatory sequential design. The findings, based on validity and reliability testing, indicate that the questionnaire instrument used has good measurement quality, with Cronbach’s alpha values exceeding 0.60 for each construct—0.84 for metacognition and 0.70 for mathematical resilience. The results also reveal that both metacognition and mathematical resilience are multidimensional constructs that complement each other. Students with strong metacognitive awareness are better able to plan, monitor, and evaluate their problem-solving strategies. At the same time, they demonstrate high perseverance, are less likely to give up, and are able to recover when facing difficulties, particularly in solving linear programming problems. This study produces a validated questionnaire instrument that can serve as a reference for future research in developing effective instructional approaches to enhance students’ abilities in applied mathematics.